ANALISIS PENGELUARAN TAHANAN DEMI HUKUM - Irmawati Ambo; Andi Purnawati; Budimah Budimah; Muliadi Muliadi (Maleo Law Journal, 2020)
The law enforcement apparatus referred to in the criminal justice system consists of a subsystem of the police, prosecutors, courts and correctional institutions which have the obligation to carry out investigations, prosecute and adjudicate the case in accordance with the prevailing laws and regulations. In carrying out these tasks, the Law of the Republic of Indonesia Number 8 of 1981 concerning Criminal Procedure Law, which is hereinafter abbreviated as (KUHAP) gives them the authority to take actions which are essentially a reduction of the human rights of the suspect as a human, such as carrying out detention.Keywords : Prisoners. For The Law